The inhibitory potential of green manure return on the germination and seedling growth of Eleusine indica L. - Zhang, Ying; Liu, Silin; Du, Xiao; Chen, Zhongwen; Ma, Zhiyu; Mu, Yinghui (Frontiers in Plant Science, 2024)
Trifolium repens L. (white clover) and Lolium perenne L. (ryegrass) are green manures widely used in conservation tillage systems worldwide. Eleusine indica L. (goosegrass) is a globally recognized noxious weed. Herein, we investigated the effects of aqueous extracts, decomposed liquids, and different straw-to-soil ratios on the germination and growth of goosegrass. The results showed that high concentrations (≥ 30%) of aqueous extracts or decomposed liquids of both green manures significantly inhibited germination-related parameters of goosegrass. The strongest inhibitory effect was observed for the 7-day decomposition treatment, and white clover's inhibitory effect was greater than the ryegrass's. A pot experiment showed that non-photochemical quenching, catalase, and peroxidase activity levels of goosegrass leaves were significantly increased. At the same time, the net photosynthetic rate significantly decreased. Seedling growth was inhibited when the straw-to-soil ratio was greater than 3:100. The ryegrass treatments inhibited goosegrass seedlings more than the white clover treatments. This study demonstrated the inhibitory potential of white clover and ryegrass straw return on seed germination and seedling growth of goosegrass. It also helped find weedresistant substances in these green manures so that their weed-control properties can be used more effectively and herbicide usage can be reduced.